ANALYSIS OF THE PSYCHOLOGICAL FOUNDATION OF THE IMPLEMENTATION OF LEARNING THE FOUR ARABIC LANGUAGE SKILLS - Ihda Filzafatin Habibah; Indah Rahmayanti; Holis Holis; Wildana Wargadinata (Kitaba, 2024)
_______Abstract: This analysis is a form of research activity that aims to re-examine a data or actual situation in the hope of increasing understanding and encouraging educators' decision making to understand several areas of psychological foundation before carrying out the learning process. The focus this time is the relationship between the psychological foundation as well as its principles in learning and the relationship between the four Arabic language skills. This research seeks to understand and present from the most specific points to the most specific in the existing theme. The approach used this time is a descriptive-qualitative-based approach using the Document studies and content analysis methods. The results of this study will later provide an overview of the material and content related to how the relationship between the principles of a theory and the psychological foundation of each person with four Arabic language skills in the present and the future.